PENGARUH SUMBER DANA DEPOSITO DAN GIRO TERHADAP TINGKAT KESEHATAN BANK (Studi Kasus Pada PT.Bank XYZ) - Sumiati Sumiati (Universitas Serang Raya, 2017)
The background of this paper is to analyze the correlation between the sources of funds of a bank's financial performance parameters including measured by CAR (Capital AdequacyRatio), ROA (Return on Assets), ROA (Operating Expenses to Operating Income) and NIM (Net Income Margin ). Measurement of the ratios above is one of the most common of Bank Indonesia in the assessment of the Bank (NKTK) or performance of the Bank.While the source of the funds is intended as funds collected from the public banks as demand deposits, and deposits as well as from inter-bank funds in connection with the intermediation function. In this case the bank acting as providers of funds to the parties who need it in the form of credit or other form of investments such as the purchase of securities and interbank placements. In setting policy on the composition or structure of the fund is ideal for banks is very important, especially as it concerns to the cost of funds, interest loans and ultimately thebank's ability to obtain the expected profit rate. This looks at ratios such as ROA and ROA, so that policies in determining the composition of improper fund structure would result inreduced level of benefits that have accrued bank and can ultimately affect the capital and soundness of the Bank.The selected research object is PT. Bank XYZ. Data collection techniques and research uses secondary data in the form of Annual Financial Statements were submitted and published by the Bank sampled. Restrictions object of research carried out in line with the title discussion namely Effect Analysis Sources and Demand Deposits to the Bank through the calculation of funding sources, by analyzing the influence of sources of funding contribution Deposits and Giro PT. Bank XYZ. Hypothesis testing program from SPSS can be seen that there are significant sources of funding and Giro deposits together with the Bank. However, based on the results of hypothesis test (t test) showed that the deposits and Giro not had a significant relationship with the Bank, meaning Giro Deposit and can not be used to estimate the value of the Bank.